An augmented reality-based SmartCard for teaching solid geometry in senior secondary schools - Hidayatsyah, Hidayatsyah; Sudirman, Sudirman; Putri, Sabila Clara; Ikhsan, Arifah Sa’diah Sakinatul (Indonesian Journal of Science and Mathematics Education, 2025)
Understanding three-dimensional geometry remains challenging for senior secondary students due to its abstract nature and the limitations of conventional 2D teaching media. This study aims to develop and evaluate an Augmented Reality (AR)-based SmartCard as an innovative learning tool to enhance conceptual understanding of solid geometry. Using the ADDIE research and development model, a limited trial was conducted with 34 Grade XI students from four schools in Lhokseumawe and North Aceh, Indonesia. Data were collected through a validated Likert-scale questionnaire assessing validity (appropriateness), practicality, and effectiveness, and analyzed descriptively using percentages. Results show the medium is very appropriate (90.3%), very practical (85.3%), and very effective (90.9%). Students positively responded to the interactive 3D visualizations, ease of use via personal smartphones, and improved spatial comprehension. The AR SmartCard successfully bridges the gap between abstract mathematical concepts and concrete visual experiences, supporting independent and engaging learning. The study concludes that this medium is a valid, practical, and effective tool for teaching solid geometry at the senior secondary level. This research has implications for providing low-cost alternative learning media that are able to bridge abstract mathematical concepts with concrete visual experiences, and can be widely adapted to school contexts with limited resources.